Undertreated Hypertension and its Implications for Public Health in Nepal: Nationwide Population-Based Survey - Koju, R; Manandhar, K; Risal, A; Steiner, TJ; Holen, A; Linde, M (Kathmandu University Medical Journal, 2015)
Background Hypertension (HTN), a major risk factor for cardiovascular diseases (CVDs), is a substantial global public health problem. Occasional studies indicate a high prevalence of HTN in the Nepalese population, but no nationwide population-based data exist so far. We opportunistically used a survey of major disorders of the brain in Nepal to measure blood pressure (BP) in participants selected randomly from the adult general population. Objective To establish the prevalence of elevated BP (eBP), and factors associated with it, regardless of any antihypertensive therapy being taken. We took this to be indicative of unmet health-care need. Method This was a cross-sectional study, conducted by unannounced household visits, employing multistage random cluster sampling. To achieve representativeness, 15 districts out of 75 in the country were investigated: one district from each of the three physiographic divisions in each of the five development regions of Nepal. One adult aged 18-65 years was selected from each household and interviewed by structured questionnaire. BP was recorded in a standardised manner by digital device (Microlife 3BM1-3®). Result From 2,109 eligible households, 2,100 adults (99.6%) participated. The prevalence of eBP (>140/90 mmHg on ?2 readings) was found to be 15.1%. Multivariate logistic regression showed significant and independent associations with demographic variables (higher age, male gender), with life-style factors (daily alcohol consumption, BMI ?25), and with living at high altitude (?2000 m). Conclusion In the context of the survey we could not collect data on antihypertensive therapy being taken but, clearly, whatever this might have been, it was failing to meet treatment needs. Almost one in six adults met criteria for hypertension, carrying risk implications for CVDs and their substantial public-health consequences. Two remediable associated factors were identified, although in a cross-sectional survey we could not prove causation. Kathmandu University Medical Journal Vol.13(1) 2015; 3-7